Biomass-derived carbon-supported Ni catalyst: an effective heterogeneous non-noble metal catalyst for the hydrogenation of nitro compounds. Issue 1 (22nd November 2019) - Tang, Qingjie; Yuan, Ziliang; Jin, Shiwei; Yao, Kaiyue; Yang, Hanmin; Chi, Quan; Liu, Bing
Abstract : The biomass-derived carbon material supported Ni catalysts (Ni/C) demonstrated a high catalytic activity for the hydrogenation of nitro compounds into primary amines at room temperature. Abstract : There has been a great deal of attention to the development of heterogeneous non-noble metal catalysts for the selective and mild hydrogenation of nitro compounds into primary amines. Herein, a biomass-derived carbon material supported Ni catalyst (Ni/C) was facilely prepared by a one-pot pyrolysis process, and the as-prepared Ni/C catalyst demonstrated a high catalytic activity for the hydrogenation of nitro compounds into primary amines at room temperature. The Ni/C catalyst not only demonstrated a high catalytic activity but also showed a good tolerance to other functional groups. Structurally diverse primary amines were achieved in yields from 92% to 99% within a few hours at room temperature under 5 bar H2 . Furthermore, the Ni/C catalyst showed good reusability without the loss of its activity.